Internationale Forschungs- und Entwicklungsstandorte - Alexander Gerybaze; Monika Schnitzer; Czernich Nina (Wirtschaftsdienst, 2013)
Die Expertenkommission Forschung und Innovation betont in ihrem aktuellen Gutachten die schnell voranschreitende Internationalisierung der Forschung und Entwicklung durch multinationale Unternehmen. Um für zukünftige technologische Entwicklungen gerüstet zu sein, empfehlen die Gutachter, die bildungspolitischen Anstrengungen und die Grundlagenforschung breit anzulegen. – – The internationalisation of research and development (R&D) is continuously increasing and will also take on steadily growing importance in the future. Firms are very mobile when deciding upon their R&D locations and choose locations where they can profit from local knowledge. In the light of the high degree of specialisation in certain technology fields by German firms while at the same time foreign firms focus their R&D activities on these very same fields, the authors recommend a broad approach for policies regarding education and basic research in order to be prepared for future technological developments.
Keywords: F23; O32; 330; Industrielle Forschung; Multinationales Unternehmen; Technischer Fortschritt; Globalisierung; Bildungspolitik; Grundlagenforschung; Forschungs- und Technologiepolitik; Deutschland